Financial Management at Muhammadiyah Educational Institutions in Banjarmasin - Riinawati Riinawati (Budapest International Research and Critics University, 2022)
The purpose of this study is to provide a descriptive analysis of the management of financial management in educational institutions. Educational institutions which are engaged in non-profit activities also carry out management processes. Educational institutions are required to carry out an optimal management process based on the concept of school-based management (SBM). SBM aims to empower schools in establishing various internal school policies that lead to improving the quality and performance of schools as a whole. Based on data collection carried out at Madrasah Aliyah Irtiqaiyah. It is based on a foundation where most of the sources of income come from the Foundation, SPP, and the government, in contrast to state schools that come from BOS. Practically speaking, the results of this article are expected to be able to provide insight into financial management in private school institutions starting from planning, implementation, recording, accountability or supervision, and reporting based on the principles of fairness, efficiency, transparency, and accountability.